Prevailing lifestyle risk factors and its association with complications among hypertensives in a rural area of Kancheepuram district in Tamil Nadu - A., Geetha; S., Gopalakrishnan; R., Umadevi (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is one of the more common non communicable diseases worldwide. There is the need for life style modifications along with the treatment for managing these diseases. But some people may continue with the lifestyle risk factors even after the occurrence of the disease, leading to complications in future. The study was planned with the objectives of identifying the prevailing lifestyle risk factors and association with blood pressure control and identifying the association between the lifestyle risk factors and complications of hypertensive patients in the study area. Methods: This is a descriptive cross sectional study done in the rural field practice area of a Medical College. Using purposive sampling technique, 300 hypertensive patients attending the rural health training centre were selected as study participant. Data collection was done by structured questionnaire. Data analysis was done using SPSS 17. Results: Among the study group, males were 54% and females were 46%. The most common life style risk factors was sedentary type physical activity (50.7%), 27% of them added extra salt to their diet, 47.7% of them were current drinkers and 31.7% of them were current smokers. About 53% had controlled hypertension and 47% had uncontrolled hypertension. Physical activity and smoking have statistically significant association with blood pressure control. All the four risk factors like sedentary lifestyle, adding extra salt, drinking and smoking had statistically significant association with complications. Conclusions: Hypertensive patients who tend to continue the lifestyle risk factors are more prone to develop uncontrolled blood pressure which in turn leads to further complications. Thus proper health education, and awareness creation programmes needs to be done for lifestyle modification, as part of intervention.